2020
DOI: 10.1088/1674-1056/ab9436
|View full text |Cite
|
Sign up to set email alerts
|

Effect of radio frequency bias on plasma characteristics of inductively coupled argon discharge based on fluid simulations*

Abstract: A fluid model is employed to investigate the effect of radio frequency bias on the behavior of an argon inductively coupled plasma (ICP). In particular, the effects of ICP source power, single-frequency bias power, and dual-frequency bias power on the characteristics of ICP are simulated at a fixed pressure of 30 mTorr (1 Torr = 1.33322 × 102 Pa). When the bias frequency is fixed at 27.12 MHz, the two-dimensional (2D) plasma density profile is significantly affected by the bias power at low ICP source power (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Their numerical model can aid in determining the optimal conditions for producing the ideal plasma. Sun et al [13,14] studied ICP plasma characteristics by using two-dimensional self-consistent fluid model. It was found that the spatial distribution of plasma characteristics was controlled by changing the bias power of single frequency bias or high frequency bias power ratio of double frequency offset.…”
Section: Introductionmentioning
confidence: 99%
“…Their numerical model can aid in determining the optimal conditions for producing the ideal plasma. Sun et al [13,14] studied ICP plasma characteristics by using two-dimensional self-consistent fluid model. It was found that the spatial distribution of plasma characteristics was controlled by changing the bias power of single frequency bias or high frequency bias power ratio of double frequency offset.…”
Section: Introductionmentioning
confidence: 99%